Vancomycin administration and AUC/MIC in patients with acute kidney injury on hemodialysis (HD): randomized clinical trial - Zamoner, Welder; Cavalcante, Ricardo de Souza; Balbi, Andre Luis; Ponce, Daniela (Springer Nature, 2024)
The pharmacokinetics and pharmacodynamics (PK/PD) of vancomycin change during HD, increasing the risk of subtherapeutic concentrations. The aim of this study was to evaluate during and after the conventional and prolonged hemodialysis sessions to identify the possible risk of the patient remaining without adequate antimicrobial coverage during therapy. Randomized, non-blind clinical trial, including critically ill adults with septic AKI on conventional (4 h) and prolonged HD (6 and 10 h) and using vancomycin for at least 72 h. Sessions were analyzed and randomized into three groups (G): control (C), dose of 15 mg/kg after session), intervention (I) 2 h (dose of 7.5 mg/kg in the second hour and 7.5 mg/kg after) and IG continuous infusion (dose of 30 mg/kg in 24 h). Of the 316 patients recruited, 87 were randomized, and 174 HD sessions were monitored. For the analysis, 28 sessions belonged to the CG, 47 to the 2-hour IG, and 31 to the continuous IG. The groups were similar in age, weight, severity scores, use of nephrotoxins, sérum albumin, Kt/V, HD modality, ultrafiltration, and intradialytic intercurrences. The intervention groups showed a higher therapeutic concentration frequency than the control group (p < 0.002). The initial concentration was identified as a risk factor (OR 1.16, p = 0.001) for a non-therapeutic vancomycin concentration in the logistic regression. In contrast, the 2-hour IG was identified as a protective factor (OR 0.24, p = 0.04). Administration of vancomycin during dialysis proved to be a protective factor against concentrations outside the therapeutic target. Further studies are needed to suggest more appropriate doses of vancomycin for patients with AKI on dialysis therapy and to assess the impact of these results on clinical outcomes.